IMAGINED IDENTITIES AND INVESTMENT: LEARNING KAZAKH IN A RUSSIAN-MEDIUM SCHOOL IN KAZAKHSTAN - Dochshanova, Saltanat (Nazarbayev University Graduate School of Education, 2022)
As part of the efforts to revitalize the Kazakh language, the Kazakhstani government has exercised specific language policies to increase the number of Kazakh speakers (Smagulova, 2021) and articulated the intentions of further linguistic development, modernization, and promotion of Kazakh in a national program (Ministry of Education and Science of the Republic of Kazakhstan, 2019). Nonetheless, despite these activities, empirical studies report disparity in Kazakh language acquisition among the students in schools with Russian medium instruction (RMI) (Gumarova, 2017) and reveal the learners’ perceived experiences of Kazakh learning in RMI schools as insufficient for the language skills development (Mukhamediyeva, 2021). Thus, the problem of teaching and learning Kazakh in the RMI context remains to be one area that requires further scholarly attention. Therefore, the purpose of this study was to explore the influence of learners’ imagined identities on their language investment through the inquiry into the schoolchildren’s experiences of learning Kazakh at a Russian-medium school in Nur-Sultan. As for the research instruments, narrative writing and semi-structured interviews were used to collect data from six student participants of Grades 10 and 11, and one Kazakh teacher. The findings demonstrated that the participants’ imagined identities appeared to be inconsistent throughout their early, middle, and present stages of learning Kazakh at school. This has subsequently resulted in differing extents of investment or disinvestment in the Kazakh language across their schooling. The study also looked into the participants’ ambivalent investment in Kazakh through the prism of the macro-level (socialization practices) and micro-level (classroom practices) drivers identified in the conceptual framework. Thus, it was revealed that micro-and macro-level variables play a substantial role in either encouraging or disabling language learners’ possibilities to develop powerful imagined identities that could potentially result in comprehensive Kazakh learning investment. Overall, taking note of the findings, the ideas for further research and pedagogical implications were made for teachers and policymakers.
Keywords: Kazakhstan; Kazakh language; Type of access: Embargo; Research Subject Categories::SOCIAL SCIENCES; national program